Teachers’ Competence in Digital Literacy in The Teaching of English at Islamic Senior High Schools - Rasyid, Fathor; Nuriyah, Wardah An (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
The objectives of this study are (1) to find out the digital literacy level of the English teachers at Islamic senior high schools, (2) the differences between public-private school English teachers' levels of digital literacy competence at the Islamic senior high school level, (3) the differences between male and female English teachers' levels of digital literacy competence of English teachers, and (4) the differences between rural and urban area English teachers' levels of digital literacy competence of English teachers. The design is descriptive comparative. 20 English teachers participated in the study. The instrument is five-scale Likert questionnaire. It is a combination of closed and open questions to elicit quantitative and qualitative data. The results indicate that the majority of English teachers' digital literacy levels in Islamic high schools are intermediate. This shows that English teachers have achieved digital literacy competence in the ability to communicate, think critically and evaluate various digital information and content on the internet, and are able to collaborate well through spaces or digital technology facilities. For the origin of schools, there are no specific gaps, but public schools have a more level of competency. Furthermore, there are quite significant differences in competence where male teachers have a higher level of digital literacy competence than female teachers in the four existing indicators. Viewed from the context of rural and urban schools, there is no specific digital literacy level gap. This indicates that teachers from rural and urban schools have commensurate levels of competence.